The Silver Lining of Price Spikes: How Electricity Price Spikes Can Help Overcome the Energy Efficiency Gap - Johannes Mauritzen (Research Institute of Industrial Economics (IFN), 2014)
Studies have shown that many consumers and businesses fail to invest in energy efficiency improvements despite seemingly ample financial incentives to do so - the so called energy efficiency gap or paradox. Attempts to explain this gap often focus on searching costs, information frictions and behavioral factors. Using data on Norwegian electricity prices and Google searches for heat pumps, I suggest that the inherently spikey nature of many electricity markets has a strong and significant positive effect on searching for information on energy efficiency goods. Because consumers pay for electricity based on at least monthly averages of the wholesale price, I can identify the informational and behavioral effect by decomposing prices into smoothed and deviation components using a novel method of measuring spikiness, comparing the actual price series with a range of deviations from Loess smoothed series.
Keywords: D12; D83; Q41; 330; Energy efficiency; Deregulated electricity markets; Price spikes; Informational frictions